Sekuritisasi Imigran Muslim dalam Kampanye dan Awal Pemerintahan Donald Trump Tahun 2015–2018 - Rifandra Aulia Rachmadi; Virtuous Setyaka; Zulkifli Harza (Palito, 2026)
This study examines the securitization process of Muslim immigrant issue in the United States during Donald Trump’s presidency. In this context, Muslim immigrants were framed as a threat to national security through a discourse constructed around associations with terrorism. Through speech acts, Trump shaped public perception to regard this issue as an existential threat requiring extraordinary measures, as outlined in the Copenhagen School’s securitization theory. This strategy was part of Trump’s political maneuver to gain electoral support in the 2016 presidential election by amplifying anti-immigrant and Islamophobic narratives. Trump’s election as president indirectly legitimized the anti-immigrant rhetoric promoted during his campaign, which was subsequently translated into a series of intimidating immigration policies. This securitization process culminated in the implementation of emergency-like measures targeting Muslim immigrants, most notably through the Travel Ban policy, which restricted entry from seven Muslim-majority countries.